2022
DOI: 10.1038/s41598-022-18422-2
|View full text |Cite
|
Sign up to set email alerts
|

Developmental RNA-Seq transcriptomics of haploid germ cells and spermatozoa uncovers novel pathways associated with teleost spermiogenesis

Abstract: In non-mammalian vertebrates, the molecular mechanisms involved in the transformation of haploid germ cells (HGCs) into spermatozoa (spermiogenesis) are largely unknown. Here, we investigated this process in the marine teleost gilthead seabream (Sparus aurata) through the examination of the changes in the transcriptome between cell-sorted HGCs and ejaculated sperm (SPZEJ). Samples were collected under strict quality controls employing immunofluorescence microscopy as well as by determining the sperm motion kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 106 publications
1
6
0
Order By: Relevance
“…The results of the previous experiments suggest the presence of Ca 2+ and K + channels in seabream spermatozoa that may play a role in the maintenance of flagellar motility. To investigate this, we carried out a meta-analysis of the data from a recent RNA-seq transcriptomic study during seabream spermiogenesis [ 30 ] in order to identify which types of ion channels are potentially expressed in the ejaculated spermatozoon. The results of this analysis revealed that seabream spermatozoa express 342 ion channel-encoding genes belonging to 38 different families of ion channels, the groups of voltage-gated K + channels (VGCCs) and voltage-gated Ca 2+ channels (VGKCs) being the most represented ( Figure 5 a, Supplementary Spreadsheet S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the previous experiments suggest the presence of Ca 2+ and K + channels in seabream spermatozoa that may play a role in the maintenance of flagellar motility. To investigate this, we carried out a meta-analysis of the data from a recent RNA-seq transcriptomic study during seabream spermiogenesis [ 30 ] in order to identify which types of ion channels are potentially expressed in the ejaculated spermatozoon. The results of this analysis revealed that seabream spermatozoa express 342 ion channel-encoding genes belonging to 38 different families of ion channels, the groups of voltage-gated K + channels (VGCCs) and voltage-gated Ca 2+ channels (VGKCs) being the most represented ( Figure 5 a, Supplementary Spreadsheet S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The transcripts from the seabream ejaculated spermatozoa transcriptome annotated as ion channels or transporters [ 30 ] were classified into different families according to the International Union of Basic and Clinical Pharmacology (IUPHAR)/British Pharmacological Society (BPS) Guide to PHARMACOLOGY ( ; accessed on 1 January 2021) [ 60 ]. The putative subcellular localization of each channel was determined using the Uniprot database ( ; accessed on 1 January 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations